Comparative videostroboscopic analysis after different external partial laryngectomies - Mumović, Gordana M. (Vojnosanitetski pregled, 2015)
Background/Aim. After external partial laryngectomias, videostroborscopy is very usefull in evaluation of postoperative phonatory mehanisms showing the “slow motion” of the vibrations of the remaining laryngeal structures. The aim of this paper was to compare the videostroboscopic characteristics of the vibration and to establish the differences in the phonation mechanisms depending on the type of external partial laryngectomy performed. Methods. This prospective study was conducted during the period 2003–2009 at the Ear, Nose and Throat Clinic, Clinical Center of Vojvodina, Novi Sad, including 99 patients with laryngeal carcinoma, treated with open surgical approach using different types of vertical and horizontal partial laryngectomy. Videostroboscopy was used to analyse vibrations of the remaining laryngeal structures. Results. The dominant vibration structure after partial horizontal laryngectomy, chordectomy, frontolateral laryngectomy and three quarter laryngectomy was the remaining vocal fold, after hemilaryngectomy it was the false vocal fold and after subtotal and near total laryngectomy it was the arythenoid. In patients with supracricoid hemilaryngopharyngectomy performed, many different structures were involved in the vibration. After most of the partial laryngectomies, vibrations can be found in the reconstructed part of the defect. In both horizontal and vertical partial laryngectomies movements of the larynx during phonation were mostly medial, while in cricohyoidoglottopexies they were anterior-posterior. Most of the operated patients (72.7%) had insufficient occlusion of the neoglottis during the phonation. Conclusion. Videostroboscopy is a useful method in examining the phonation mechanisms of reconstructed laryngeal structures after partial laryngectomy as well as in planning postoperative voice therapy.